Soil Properties from Low-Velocity Probe Penetration - Jerome B. Johnson; James D. Cargile; Donald M. Smith (Shock and Vibration)
A physical model of low-velocity probe penetration is developed to characterize soil by type, strength, maximum compaction, and initial density using Newton's second law to describe the processes controlling probe momentum loss. The probe loses momentum by causing soil failure (strength), accelerating and compacting soil around the probe (inertia), and through frictional sliding at the probe/soil interface (friction). Probe geometry, mass, and impact velocity influences are incorporated into the model. Model predictions of probe deceleration history and depth of penetration agree well with experiments, without the need for free variables or complex numerical simulations.